(untitled) - Jackson, Andrew R W. (London, 1996)
The book provides a clear and authoritative introduction to the fundamental concepts and vocabulary necessary to explore complex environmental issues and phenomena. It is divided into two parts. The first examines the natural environment in the absence of human activity. The second reviews the environmental in the consequences of the exploitation of natural resources and includes individual chapters devoted to water pollution, atmospheric pollution and waste management
Keywords: Natural resources,Pollution; Environmental aspects,Environmental aspects